Utilizing Ex-Bird Market Buildings in the City of Balikpapan: Needs and Economics Approach Analysis - Zahrul Azhar bin Nasir; Anisa Nurpita; Agusta Ika Prihanti Nugraheni (Universitas Ahmad Dahlan, Yogyakarta, 2023)
Balikpapan City has many active markets but there are also markets that are no longer active, one of which is the former Bird Market building. The purpose of this study is to analyse the needs and economics of the asset in order to achieve the most optimal management. Alternative economic studies are based on the results of FGDs and surveys to fulfil the wishes of the community. The data used is primary data using a survey where the respondents are the community around the asset location and supported by stakeholders. The analytical tools used are BCR (Benefit Cost Ratio) and NPV (Net Present Value). The results obtained are the most profitable alternative economic use is a children's amusement park with an NPV value of -19.6 billion rupiah and a BCR value of 1.71, followed by the UMKM Center building with an NPV value of 3.3 billion rupiah and a BCR value of 1.17 or more than 1. Meanwhile, the first priority of community needs is the traditional market, the second is the UMKM center building. So the alternative that suits the needs of the community and has economic benefits is the UMKM centre building. Therefore, based on the results of economic calculations, it is recommended that the former bird market building be better used for the UMKM centre. Thus, the local government can use this research as a reference in determining the reuse of the former bird market building.